Peningkatan Kapasitas Peternak Itik melalui Pelatihan Fermentasi Azolla dan Ampas Sagu untuk Inovasi Pakan Ramah Lingkungan - Andi Tenri Bau Astuti Mahmud; Santi, Santi; Agustina; Muhammad Arman Yamin Pagala; Sri Nengsih (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community engagement program aimed to enhance the knowledge and technical skills of duck farmers in utilizing locally available resources such as Azolla pinnata and sago pulp as alternative fermented feed ingredients in Bakka-Bakka Village, Wonomulyo District, Polewali Mandar Regency. The activity was implemented using a participatory action research approach through four stages: socialization, theoretical and practical training on fermented feed production, field mentoring, and evaluation. The evaluation employed a pre-test and post-test design involving 25 duck farmers to assess their improvement in knowledge and practical skills related to local feed fermentation technology. The results indicated a significant increase in farmers’ knowledge, from 78% before the training to 96% after the training, categorized as very good. The fermented feed produced contained 15–18% crude protein and demonstrated improved biological relevance by enhancing feed efficiency and duck growth while reducing production costs compared to commercial feed. The program not only strengthened farmers’ technical competence but also fostered the establishment of independent farmer groups committed to implementing environmentally friendly feed innovations. Overall, this activity effectively supported the development of sustainable duck farming systems based on local resources and contributed to achieving food self-sufficiency and a circular rural economy.